La necropoli romana di Melano (canton Ticino - Svizzera) : struttura e cronologia, tipologia delle sepolture, corredi funerari e materiali : il castello e il castellaccio di Melano - De Micheli Schulthess, Christiane M. A., (Access archaeology., 2021)
The Roman necropolis of Melano (Switzerland), excavated 1957-1979, is one of the few discovered in the Sottoceneri region, where the findings are mostly isolated burials or those in small groups. It consists of 26 cremation and inhumation tombs and stands out for its variety of types and the materials used in their construction.